Serial measurement of lipid profile and inflammatory markers in patients with acute myocardial infarction - Shrivastava, Amit Kumar; Singh, Harsh Vardhan; Raizada, Arun; Singh, Sanjeev Kumar (Technische Universität Dortmund, 2015)
Serum concentration of lipids and lipoproteins changes during the course of acute coronary syndrome as a consequence of the inflammatory response. The objective of this study was to evaluate the effect of acute myocardial infarction (AMI) on the levels of lipid profile and inflammatory markers. We investigated 400 patients with AMI who were admitted within 24 h of onset of symptoms. Serum levels of total cholesterol (TC), triglyceride (TG), low density lipoprotein (LDL) and high density lipoprotein (HDL) were determined by standard enzymatic methods along with high sensitive C-reactive protein (hs-CRP) (latex enhanced immunoturbidimetric assay) and cytokines, interleukin (IL)-6 and IL-10 (quantitative ‘‘sandwich’’ enzyme-linked immunosorbent assay). The results indicate a trend of reduced TC, LDL, and HDL, and elevated TG levels, along with pro- and anti-inflammatory markers (p < 0.001), between day 1 and the day 2 serum samples of AMI patients. However, corrections in the serum levels have been observed at day 7. Our results demonstrate significant variations in the mean lipid levels and inflammatory markers between days 1, 2 and 7 after AMI. Therefore, it is recommended that the serum lipids should be assessed within 24 hours after infarction. Early treatment of hyperlipidemia provides potential benefits. Exact knowledge regarding baseline serum lipids and lipoprotein levels as well as their varying characteristics can provide a rational basis for clinical decisions about lipid lowering therapy.
EXCLI Journal;Vol. 14, 2015
Keywords: acute myocardial infarction; lipid profile; inflammatory markers; serial measurement; 610